Tell Me With Pictures! Grade 8 Students’ Digital Representations of Engagement in Learning - Scheffel, Tara-Lynn (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2017)
This article discusses what constitutes engagement in learning from the perspective of Grade 8 students. While a mixed methods approach was employed to gather quantitative and qualitative data, the focus of this article is the qualitative data collected from an interactive, participatory workshop. As part of this workshop, Grade 8 students were asked to capture moments of engagement by taking digital pictures of spaces, places, items, and activities that represented their engagement in learning. Analysis of the digital pictures revealed themes related to: interest, collaboration, inspiration/motivation, nourishment, enjoyment, discovery, and a future purpose. Each theme is discussed with supporting pictures and quotes to prompt reflection and raise critical questions from the viewpoint of learners.